The economic impact of asymmetric warfare through illicit drug trafficking in Indonesia - Beny Abukhaer Tatara; Suhirwan Suhirwan; Mochammad Afifuddin (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This research aims to analyze the economic impact of asymmetric warfare through illicit drug trafficking in Indonesia.Method — This research uses a qualitative method with data collection techniques using interviews and literature studies. Researchers conduct interviews with officials related to the National Narcotics Board with 10 people and officials from the Defense Potential Directorate of the Indonesian Ministry of Defense with 2 people.Result — Illicit drug trafficking in Indonesia has an impact on the national resilience of the Indonesian nation. The impact covers all aspects of astagatra, which consists of trigatra aspects, namely demographic, geographical, and natural resources aspects, and pancagatra aspects, which consist of ideological, political, economic, socio-cultural, and defense-security aspects. In economics, research has shown that the economic loss due to drugs amounts to 84.7 trillion rupiahs due to illicit drug trafficking, where 77.42 trillion rupiahs is a personal loss and 7.27 trillion rupiahs is a social cost. Moreover, drug addicts will find it difficult to get a job, given that the impact of rejection from the community and the work environment reaches 92%. Cooperation between agencies and community participation is necessary to address it. This is because Indonesia's defense system is total people's defense and security system (Sishankamrata), which requires the participation of all components of the nation.Contribution — This research add to the knowledge about the impact of asymmetric warfare through illicit drug trafficking, specifically the economic impact. In addition, this research is expected to be a source of input for the government in developing strategic steps to counter illicit drug trafficking which is asymmetric warfare.